Analisis Perhitungan Pajak Penghasilan Pasal 25 Pada PT. Mopoli Raya - Surya Sanjaya; M. Reza Pratama (CERED Indonesia Institute, 2022)
This stud Type the data used is quantitative. Sources of data used are primary data and secondary data. Data collection technique is documentation. Data analysis technique is descriptive analysis technique. The results of the analysis of the financial statements show that there are recreation costs, cellphone and mobile phone fees, and newspaper & magazine costs that are not related to the company's activities that were not corrected by the company in 2017 resulting in a difference in the amount of taxable profit before the fiscal correction and after the fiscal correction. . The difference in the amount of taxable profit results in different income taxes payable, different amounts of article 25 income tax credits and different amounts of underpaid taxes..